Communication Strategies of the Online Mobile Legend Gaming Community: Source Queens Racing (SQRC) Esport: Strategi Komunikasi Komunitas Game Online Mobile Legend Source Quenns Racing (SQRC) Esport - Pangestu, M Rafly Indra (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the communication patterns within the Mobile Legend Esport community in Pasuruan, employing Miles and Huberman's analysis. The findings reveal that the community primarily exhibits an interpersonal communication pattern characterized by (a) Openness, where members are transparent and accountable in their information sharing; (b) Empathy, as players consistently demonstrate solidarity and empathy towards one another; (c) Support, with players offering mutual assistance; (d) Positive feelings, evidenced by moral support and enthusiasm for fellow players; and (e) Equality, observed in the coach's equitable distribution of game knowledge to all players. These findings shed light on the dynamics of interpersonal communication within gaming communities and have implications for fostering positive relationships and support networks among Esport enthusiasts globally. Highlights: Interpersonal communication fosters solidarity and empathy within gaming communities. Equality in knowledge sharing promotes inclusive Esport participation. Positive feelings and support enhance players' experiences and performance. Keywords: Mobile Legend, Esport, Communication Patterns, Interpersonal, Pasuruan